Economic evidence with respect to cost-effectiveness of the transitional care model among geriatric patients discharged from hospital to home: a systematic review - Kristina Kast; Carl-Philipp Wachter; Oliver Schöffski; Martina Rimmele (The European Journal of Health Economics, 2021)
Background: The German hospital-to-home discharge management of geriatric patients has long been criticized. The implementation of the American Transitional Care Model (TCM) could help to reduce readmissions and costs. The objective of this review was to check the scientific evidence of the cost-effectiveness of the TCM. Methods A systematic literature search in six databases for the time period of 26~years was conducted. The studies had to meet all pre-defined inclusion criteria. The data extraction is based on a criteria chart from literature. The methodological quality was assessed using the tools of the National Heart, Lung, and Blood Institute as well as the Consensus Health Economic Criteria list. The results transferability to German health care system was explained based on the criteria from the literature. Results Three American studies met all criteria. They showed partial cost analyses but no full economic analyses. It could be assumed that the economic effect of the TCM changes over time. The costs of a care coordinator could not be determined because few detailed information was reported. The TCM may have negative consequences for hospitals. The results are not transferable to Germany. Conclusion There is no scientific evidence for the cost-effectiveness of the defined TCM. The optimal TCM duration still needs to be clarified. A detailed overview with units and prices and an additional consideration of the hospital perspective could help to make the information more transparent when deciding about the TCM implementation. A full economic analysis under German conditions or for similar European countries is necessary.
Keywords: I1; 610; Transitional care; Geriatric patients; Hospital discharge; Cost-effectiveness; Economic analysis; Budget impact analysis